PEMANFAATAN GOOGLE FORM DAN GOOGLE SHEET DALAM PEMBELAJARAN - Siregar, Reni; Nazara, Indah Trisdayanti; Saragi, Christina Natalina; Situmorang, Joel Dani (Merwinspy Publisher, 2024)
The implementation of this PKM application is the socialisation of the use of google form for teachers at YPI Dharma Budi High School. The purpose of this activity is based on the results of observations and initial interviews with the principal and teachers, students bring the socialization of the use of google space because at that location it is still very necessary to use technology to be evenly distributed. In addition, students will also participate in the classroom teaching process if there are empty classes and teach according to the student's study programme. The results of this PKM program helped the school in completing administration and utilizing google forms in the learning process and inputting student data. Students also get additional insights from the use of google form.